Automatic car parking for a scale model car - Chaves Rodríguez, José Pablo (2020)
There is a problem for many car users which is to maneuver the vehicle is in parking eitherbattery or in parallel, it is given that many people take a long time to park, generates stress andin some cases to them it is impossible to park, and those who fail can perform this maneuver sobad wasting space or leaving other vehicles with the inability to leave where they are parked.Because of this the Department of measurement - Aeronautical Instrumentation Laboratory ofthe Czech Technical University in Prague (Czech Technical University in Prague) has decidedto make an automatic parking applied first to a scale model car where the system is ableto recognize where is available parking space, once identified this, the car must performautonomously parking maneuver without any assistance from the driver.This system should take into account the directional control of the vehicle, the displacementin any direction, at the same time must be able to recognize the distance between the objectsaround the vehicle, identify when next to a space enough parking shaped battery and finallybe able to avoid collisions with objects or obstacles that are presented in front and behind thevehicle and maintain a minimum safety distance against them.